KOMPOSISI DAN KEPADATAN SEED BANK GULMA PADA BERBAGAI KEDALAMAN TANAH PERTANAMAN PALAWIJA BALAI BENIH INDUK TANJUNG SELAMAT - Marshal P. Siahaan; Edison Purba; Teuku Irmansyah (Universitas Sumatera Utara, 2014)
Weed seeds in the soil per hectare can reach millions of amount and consists of many differentspecies. The depth of the weed seeds can be used as indicator of competitive level between crop andweeds. The research aims to determine the composition and density of seed bank at various level ofsoil depths at “ Balai Benih Palawija ” Tanjung Selamat North Sumatra. Soil Samples warecollected from four soil depths, namely: 0-5 cm, 5-10 cm, 10-15 cm,15-20 cm using metal pipe withdiameter of 3 cm. The parameters measured were the number of weeds that grow by the depth ofsoil, weed composition (%) per depth of soil and weeds growing time per depth of soil.From resultshowed that the highest density of weed seed bank is found at the depth of 0 – 5 cm. Weedcomposition dominated ( 68.9 % ) by broadleaf weeds. There are differences in the composition anddensity of the real seed bank at different depths in the soil in the field area of Balai Benih IndukTanjung Selamat. Composition and density of weed tends to be lower in deeper soil depths.Keywords: seed bank, depth of soil and crops planting area